Seed removal, seed dispersers, and the allocation of tissues in Myrtaceae seeds - Béllo Carvalho, Rodrigo; Pizo, Marco A. [UNESP] (Wiley, 2023)
To avoid seed predation, plants may invest in protective seed tissues. Often related to seed size, allocation in seeds' physical defenses can also be influenced by dispersers. We explore the relationships between seed traits (seed mass and hardness) and seed removal in 22 Myrtaceae species of the Brazilian Atlantic Forest, a dominant and diverse fleshy-fruited taxon dispersed by birds, rodents, and other mammals. Our goal is to understand how seed traits influence seed removal rates, and whether dispersers can affect tissue allocation in the seed coat. Seeds were exposed to field removal experiments. In the laboratory, total seed mass and seed coat mass were obtained. To evaluate the influence of seed traits on removal, we performed Kruskal–Wallis and Simple Linear Regression tests. We assessed seed coat and seed mass covariation through standardized major-axis allometric regressions. Harder seeds were larger than softer ones. Seed traits affect removal rates, as tougher and heavier seeds had lower removal. Seed mass significantly predicts seed coat proportion in seven of the 14 species tested. Bird-dispersed species tend to exhibit lower proportions of seed coat as seed mass increases, whereas rodent-dispersed species apparently present the opposite trend, with seed coat proportion increasing with seed mass. Such difference may be caused by the contrasting seed predation pressure represented by birds and rodents. Energy allocation for defense, expressed in seed coat proportion, is greater in large seeds, as these are mostly dispersed by rodents whose propensity to cache and disperse seeds is greater for large and well-protected seeds.
Keywords: allometry; Brazilian Atlantic Forest; rodents; seed coat; seed predation; seed size